Diversification of terpenoid emissions proposes a geographic structure based on climate and pathogen composition in Japanese cedar - Tsutom Hiura (Nature Portfolio, 2021)
Abstract Biogenic volatile organic compounds emitted from plants are important constituents of atmospheric chemistry and play a major role in the resistance of plants against various environmental stresses. However, little is known about how abiotic and biotic environments on a geographic scale relate to diversifications of the emission. Here, we present variations of terpenes stored in and emitted from leaves of a single species in a common garden, using genetically differentiated local populations of Japanese cedar, the most dominant and widely distributed tree species in Japan. Furthermore, we determined the composition of fungal communities in 50 locations, based on the presence or absence of 158 fungal species inhabiting the cedar. The results showed that terpenoids, especially those that are emitted, were highly diversified and geographically structured among the 12 populations. The total amount of stored terpenes was negatively affected by warm and less-snow climates. On the other hand, variations in some emitted terpenoid species among the populations were correlated to antagonistic fungal species inhabiting the Japanese cedar. We propose that the diversification of composition and amount of stored and emitted terpenoids in the tree species is not only structured by climate, but also antagonistic fungal communities through biological interactions.